Business Ethics Violation on Hit Products in the Practical Gorund of PT Megasari Makmur: Halal Perspective Analysis - Muhtadi Muhtadi; Muhammad Said (International Journal of Social Service and Research, 2023)
The rise of cases of violations of business ethics cases, one of which was by PT. Megarsari Makmur who committed an act of violation that had a major impact on consumers because it had endangered consumers by adding two dangerous chemicals and not applying detailed ingredient information on product labels. The research method used is a descriptive qualitative method that utilizes data collection techniques for literature and document studies. PT. Megarsari Makmur is more concerned with personal gain by keeping production costs as low as possible, however, it is detrimental to many parties. The purpose of this research is to examine further about the problem analysis and the solution chosen by PT. Megarsari Makmur based on a review of the halal industry. The chosen form of problem solving is by withdrawing all HIT products that have been spread throughout the market